Pelestarian Adat Istiadat Masyarakat Baduy di Era Modernisasi - Yunita Yunita; Raden Rahma Restu Maulida; Naufalia Putri; Dede Nadien Rahmadini; Desi Hermawati (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The Baduy community located in Lebak Regency, Banten, is an ethnic group that still maintains its customs even today amidst the wave of modernization. This research aims to explore how the Baduy people preserve their customs and traditions as well as the challenges they face in facing changing times. In the era of globalization and modernization which has brought advances in technology and foreign culture, the Baduy people continue to maintain their cultural identity, especially through the principles of simple and sustainable living. This research uses qualitative methods combined with interview techniques and participant observation to understand their practices in preserving customs and traditions. The research results show that the preservation of Baduy customs is not only achieved through religious rituals but also the way they organize their socio-economic life, for example in an agricultural system that respects the environment and a lifestyle that prioritizes simplicity. However, big challenges come from technological developments, economic changes and increasingly strong external cultural influences.